In vitro and in vivo evaluation of anti-inflammatory activities of ethanol extract from Lom-Am-Ma-Pruek remedy for pain relief - Arunporn Itharat; Pun Thongmee; Krit Piwngam; Janjira Inprasit; Sunita Makchuchit; Pranporn Kuropakornpong; Neal M. Davies (Research in Pharmaceutical Sciences)
Background and purpose: Lom-Am-Ma-Pruek (LAMP) remedy has been used in Thai traditional medicine to relieve pain associated with the inflammatory process. The anti-inflammatory activity and bioactivity of LAMP in an animal model have not been previously investigated. We evaluated the in-vitro and in-vivo anti-inflammatory activity of LAMP ethanol extract. Experimental approach: The anti-inflammatory activity of LAMP and its plant ingredients were investigated on lipopolysaccharide-stimulated NO, PGE2, and TNF-α release from RAW264.7 cells. Furthermore, the stability of LAMP under biological and chemical accelerated conditions was evaluated using the Griess reaction assay and HPLC. Lastly, rat models with ethyl phenylpropionate (EPP)-induced ear edema and carrageenan-induced paw edema were utilized to assess anti-inflammatory activity. Findings/Results: LAMP possessed potent inhibitory effects on NO, PGE2, and TNF-α production with IC50 values of 24.90 ± 0.86, 4.77 ± 0.03, and 35.01 ± 2.61 µg/mL, respectively. In addition, LAMP extract demonstrated stable biological activity, anti-inflammatory effects, and phytochemical content stability under stress conditions. Additionally, 0.5%, 1%, and 2% w/v LAMP significantly inhibited EPP-induced rat ear edema over time equivalent to 5% w/v phenylbutazone. LAMP at 180, 375, and 750 mg/kg also considerably reduced carrageenan-induced rat paw edema 2 h after carrageenan administration compared to phenylbutazone at 250 mg/kg. Conclusion and implications: LAMP has anti-inflammatory activity by inhibiting PGE2 formation. These findings are consistent with the efficacy and traditional use of the LAMP remedy in treating inflammatory diseases.